The ratio of population to certain aspects of sports and recreational activities - Wang Xue Man (Kharkov National Pedagogical University, 2010)
We consider the opinion of the population of some aspects of sports and recreational activities. A survey revealed that most respondents are aware of the importance of exercise in the process of formation of physical health. Also, the majority of respondents willing to participate directly in sports and recreational activities. A total of 188 questionnaires have involved residents of the city Kharkov aged 25 - 40 years.